Analisis Partisipasi Masyarakat dalam Pengelolaan Sampah di Kecamatan Tuah Madani Kota Pekanbaru - Rahmi Febrianti; Ratna Dewi; Ainun Mardiah (Policy, Law and Political Research Center, 2022)
This research explains about community participation in waste management in Tuah Madani District, Pekanbaru City, this research was conducted in Tuah Madani District. The aims of this study are, 1) to find out the form of community participation in waste management in Pekanbaru City District, and 2) to find out the factors that influence community participation in waste management in Tuah Madani District, Pekanbaru City. The informants involved in this research are the Camat, Head of RT, Community, and Waste Bank Management Coordination. This study uses the concept of Regional Regulation Number 08 of 2014 concerning Waste Management. Data collection techniques used were interviews, observations and documentation, while for data analysis used qualitative descriptive techniques with data collection techniques using open interview techniques, observation and field documentation studies. Based on the results of the study, it shows that community participation is categorized as moderate, meaning that the community participates but in implementation, it is still not said to be maximal. Community participation is carried out by doing mutual cooperation and transportation is carried out in the morning and afternoon, twice a week. And there are several factors that influence it, including the character of the residents who don't care, and the location of the Garbage Bank which is far away